Proactive school security and emergency preparedness planning - Trump, Kenneth S.; Sage eBooks (Thousand Oaks, Calif. : Corwin ; London : SAGE, 2011)
Security expert Kenneth S. Trump outlines school security issues and provides nuts-and-bolts strategies for preventing violence and preparing for crises. Includes a companion website.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Schools -- Security measures -- United States -- Handbooks, manuals, etc; Schools -- United States -- Safety measures -- Handbooks, manuals, etc; School crisis management -- United States -- Handbooks, manuals, etc; Electronic books